The Challenges of Child and Adolescent Psychiatrists in the Process of the Disability Report Evaluation - Esin, İbrahim Selçuk; Öğütlü, Hakan; Büyükdeniz, Ayşe; Babadağı, Zehra; Dursun, Onur Burak; Başgül, Ş. Senem (My University, 2020)
This study aimed to identify the challenges facedby child and adolescent psychiatrists on reportingIntellectual & Developmental Disability during thedisability evaluation process in Turkey, One hundredfive child and adolescent psychiatrists agreed toparticipate in the study. We asked them to complete anonline questionnaire that was prepared for this study.The major challenge of the process was determiningwhether the disability is severe or not. On the otherhand, the age range that the participants had the mostdifficulty in the process was preschool. As a result,child and adolescent psychiatrist had essentialdifficulties while evaluating children with Intellectual& Developmental Disabilities. As a solution, medicaldiagnosis and functionality should be evaluatedtogether in order to determine the disability level andwhether disability is severe or not.

Bu çalışma, çocuk ve ergen psikiyatrlarının Türkiye'de özel gereksinimi değerlendirme sürecinde Entellektüel Yeti Yitimi ve Bilişsel Gelişim Geriliği’ni raporlamada karşılaştıkları zorlukları tespit etmeyi amaçlamıştır. Yüz beş çocuk ve ergen psikiyatrist çalışmaya katılmayı kabul etti. Katılımcılardan, bu çalışma için hazırlanan çevrimiçi bir anketi doldurmaları istendi. Katılımcılar, sürecin kendileri için en büyük zorluğunun gereksinimin ciddi olup olmadığının belirlenmesi olduğunu belirttiler. Öte yandan, katılımcıların bu süreçte en fazla zorluk yaşadığı yaş aralığı okulöncesi idi. Sonuç olarak, çocuk ve ergen psikiyatristleri Entellektüel Yeti Yitimi ve Bilişsel Gelişim Geriliği tanılı çocukları değerlendirirken önemli zorluklarla karşılaşmıştır. Çözüm olarak, gereksinim düzeyini ve gereksinimin şiddetli olup olmadığını belirlemek için tıbbi tanı ve işlevsellik birlikte değerlendirilmesi gereklidir.
Heyet Raporu Değerlendirme Sürecinde Çocuk ve Ergen Psikiyatristlerin Yaşadıkları Zorluklar
Keywords: bilişsel; gelişim; gerilik; çocuk; ergen; psikiyatri; raporlama